Sabbath as the Way to Shalom in the Biblical Tradition - Finkel, Asher (Journal of Dharma, 1986)
The Biblical word for peace in Hebrew, Shalom, does not connote only a cessation of conflict and end of war. Its meaning points to completion, wholesomeness and the achievement of perfection. Thus, the pedagogical aim of the Torah, the Pentateuchal tradition and legislation, is to guide the people in the paths of Shalom (Prov 3:17). God in the revealed scriptures intends for the person, singular or collective, to pursue Shalom, as the only road to harmonious relationship with the Creator, whose very attribute is Shalom (Jud 6:24). The only blessing that God’s people can truly enjoy is the blessing of Shalom (Ps 29:11), as a divine gift that produces human enrichment and wholesome living. The Rabbinic tradition exalts the ideal Shalom l and applies its principle in socio-religious legislation (Misnah Aboth I : 18). The very teaching of Jesus in the Sermon on the Mount expresses the same: "Blessed are the pursuers of peace (Shalom), for they are called the sons of God" (Matt 5:9). This life style can indeed be achieved, if only "you shall be perfect (Shalem) as your father in Heaven is perfect" (5:48). The dynamic application of the ruler of imitatio Dei in human conduct culminates in the pursuit of Shalom in fellowship with God.